Neurotoxicity with high-dose disulfiram and vorinostat used for HIV latency reversal. (1st January 2022) - McMahon, James H.; Evans, Vanessa A.; Lau, Jillian S.Y.; Symons, Jori; Zerbato, Jennifer M.; Chang, Judy; Solomon, Ajantha; Tennakoon, Surekha; Dantanarayana, Ashanti; Hagenauer, Michelle; Lee, Sulggi; Palmer, Sarah; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to examine whether administering both vorinostat and disulfiram to people with HIV (PWH) on antiretroviral therapy (ART) is well tolerated and can enhance HIV latency reversal. Design: Vorinostat and disulfiram can increase HIV transcription in PWH on ART. Together, these agents may lead to significant HIV latency reversal. Methods: Virologically suppressed PWH on ART received disulfiram 2000 mg daily for 28 days and vorinostat 400 mg daily on days 8–10 and 22–24. The primary endpoint was plasma HIV RNA on day 11 relative to baseline using a single copy assay. Assessments included cell-associated unspliced RNA as a marker of latency reversal, HIV DNA in CD4 + T-cells, plasma HIV RNA, and plasma concentrations of ART, vorinostat, and disulfiram. Results: The first two participants (P1 and P2) experienced grade 3 neurotoxicity leading to trial suspension. After 24 days, P1 presented with confusion, lethargy, and ataxia having stopped disulfiram and ART. Symptoms resolved by day 29. After 11 days, P2 presented with paranoia, emotional lability, lethargy, ataxia, and study drugs were ceased. Symptoms resolved by day 23. CA-US RNA increased by 1.4-fold and 1.3-fold for P1 and P2 respectively. Plasma HIV RNA was detectable from day 8 to 37 (peak 81 copies ml −1 ) for P2 but was not increased in P1 Antiretroviral levels were therapeutic and neuronal injury markers were elevated in P1. Conclusion: The combination of prolonged high-dose disulfiram and vorinostat was not safe in PWH on ART and should not be pursued despite evidence of latency reversal.